Surrogate Mother (Ibu Pengganti) Dalam Pengaturan Hukum Positif di Indonesia - Naomi, Valerie Liony Yuliana; Affandi, Imanudin (Peneliti.net, 2024)
In general, there is still a lot of accumulation of disputes in court through the courts, this is not in accordance with the principle of a fast, simple and low-cost trial. If this principle is not implemented properly, it will have an impact on the accumulation of disputes in court. With so many hoarding of disputes in court, an alternative dispute resolution is needed that can reduce the buildup of conflict in court. Mediation is an alternative form of dispute resolution that grows and develops along with the development of the human desire to resolve disputes quickly and satisfy the parties to the dispute. Currently, mediation is being developed in court to resolve disputes reinforced by PERMA No. 1 of 2016 concerning Procedures for Mediation in Courts. Mediation is one of the efforts that can be made to resolve conflicts in which the disputing parties agree to present an independent third party to act as a mediator. The mediator must be neutral, impartial to one of the parties and not intervene in the mediation process.